Metabolic Syndrome in Psoriasis Is Associated With Upregulation of CXCL16 on Monocytes and a Dysbalance in Innate Lymphoid Cells - Schielke, Lisa; Zimmermann, Nick; Hobelsberger, Sarah; Steininger, Julian; Strunk, Anne; Blau, Kristin; Hernandez, Jessica; Künzel, Stephan; Ziegenbalg, Robert; Rösing, Sarah; Beissert, Stefan; Abraham, Susanne; et al. (Frontiers in Immunology, 2022)
Psoriasis is frequently associated with the metabolic syndrome and occurs more often in obese individuals. In order to understand innate immune mechanisms mediating this inflammatory pattern we investigated expression of the chemokine and lipid scavenger receptor CXCL16 in patients with psoriasis and associated comorbidities. CXCL16 expression was enhanced on all monocyte subsets in psoriatic patients compared with healthy controls and positively correlated with psoriasis activity and severity index, body mass index and the risk for cardiovascular disease indicated by PROCAM score. The intensity of CXCL16 expression on monocytes further correlated with their capability to phagocytose oxidized LDL indicating the possibility to transform into foam cells in atherosclerotic plaques. Patients with psoriasis and atherosclerosis or obesity displayed elevated numbers of innate lymphoid cells in blood with specific increase of the IFNgamma or IL-17 producing ILC1 and ILC3 subpopulations. The expression of the CXCL16 receptor CXCR6 was increased in ILCs and co-expressed with CCR6 but not CCR7 indicating their migratory potential to psoriatic skin or adipose tissue that is characterized by strong CXCL16 and CCL20 expression. This hypothesis was supported by the finding that the percentage of CXCR6 expressing ILCs was alleviated in blood of psoriatic patients. Together these data link a strong expression of CXCL16 to metabolic syndrome in psoriasis and indicate a possible link to ILC activation and tissue distribution in obese psoriatic patients. These data contribute to the understanding of the complex interaction of innate immunity and metabolic state in psoriasis.